Crowd of people waiting for mail at Dawson Post Office, showing log buildings and sign for mine broker's office, ca. 1898 - Nowell, Frank H., 1864-1950 (1898)
Caption on image: Waiting for mail at Dawson City Post Office. Photo by F.H. Nowell, 1985 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number